The Interaction of Pre-programmed Eye Movements With the Vestibulo-Ocular Reflex - Haggerty, Stephanie E.; King, W. Michael (Frontiers in Systems Neuroscience, 2018)
The vestibular-ocular reflex (VOR) works to stabilize gaze during unexpected head movements. However, even subjects who lack a VOR (e.g. vestibulopathic patients) can achieve gaze stability during planned head movements by using pre-programmed eye movements (PPEM). The extent to which PPEM are used by healthy intact subjects and how they interact with the VOR is still unclear. We propose a model of gaze stabilization which makes several claims: 1) the VOR provides ocular stability during unexpected (i.e. passive) head movements; 2) PPEM are used by both healthy and vestibulopathic subjects during planned (i.e. active) head movements; and 3) when a passive perturbation interrupts an active head movement in intact animals (i.e. combined passive and active head movement) the VOR works with PPEM to provide compensation. First, we show how our model can reconcile some seemingly conflicting findings in earlier literature. We then test the above-mentioned predictions against data we collected from both healthy and vestibular-lesioned guinea pigs. We found that 1) vestibular-lesioned animals showed a dramatic decrease in compensatory eye movements during passive head movements, 2) both populations showed improved ocular compensation during active vs. passive head movements and 3) during combined active and passive head movements, eye movements compensated for both the active and passive component of head velocity. These results support our hypothesis that while the VOR provides compensation during passive head movements, PPEM are used by both intact and lesioned subjects during active movements and, further, that PPEM work together with the VOR to achieve gaze stability.